Range extension for Eupiestus spinifer Fauvel in China (Coleoptera: Staphylinidae: Piestinae) - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2016)
Eupiestus spinifer Fauvel, 1895 is newly recorded from China (Yunnan Province). The habitus and morphological details of this species are illustrated for the first time.